EVERYDAY RESISTANCE IN MAKING ONESELF VISIBLE: YOUNG ADULTS’ NEGOTIATIONS WITH INSTITUTIONAL SOCIAL CONTROL IN YOUTH SERVICES - Kallio, Jenni; Honkatukia, Päivi (International Journal of Child, Youth and Family Studies, 2022)
This article concerns young adults’ institutional encounters with professionals in the context of youth services. The encounters are analyzed as institutional social control — the practices and mechanisms that steer young people’s conduct in accordance with the normative order. We make visible young adults’ acts of everyday resistance as they negotiate, problematize, and challenge aspects of institutional social control. The data consist of 17 life-course interviews with young adults aged 18 to 24 who visited youth shelters organized by the Finnish Red Cross. Participants expressed criticism of the normative expectations and the categorizing and controlling practices that they encountered. However, there is a danger that in the institutional encounters, their acts of everyday resistance are not acknowledged as political agency; instead, stereotypical notions strengthen the interpretation of the young adults as problematic or in need of protection. This lack of recognition may contribute to increased vulnerability in the young people the institutions are intended to support them.